The Role of Digital Marketing in Increasing MSME Sales Growth - Balenggon, Kurniawan; Zaharah, Zakiyah; Syarifuddin, Umar; Wanti, Sri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the role of digital marketing in boosting the sales growth of UMKM Ummu Khalif, a culinary business specializing in traditional Palu sambal. In response to the digital era, UMKM Ummu Khalif leverages various digital platforms such as Facebook, Instagram, WhatsApp Business, TikTok, and Shopee to expand its market reach and increase sales volume. The research employs a qualitative method with data collection techniques including interviews, observations, and documentation. The findings reveal that WhatsApp Business is the most effective platform for driving direct transactions, contributing to the sale of up to 200 bottles of sambal per month. Meanwhile, Instagram and TikTok play crucial roles in enhancing brand awareness through engaging visual content, such as sambal-making processes, customer testimonials, and promotional activities during exhibitions. The synergy between creative promotional content and the strategic selection of digital platforms has proven to boost sales by up to 50% compared to the period before the intensive application of digital marketing. However, UMKM Ummu Khalif faces several challenges, including limited time for consistent content creation, a lack of human resources, and insufficient in-depth understanding of optimal strategies for each platform. This study emphasizes that effective and adaptive digital marketing strategies significantly contribute to UMKM growth in the post-pandemic era, where consumer behavior and digital platform trends continue to evolve. Furthermore, this study offers academic contributions by addressing research gaps related to digital marketing implementation in sambal-based culinary MSMEs, while highlighting the importance of integrating social media and marketplaces as part of a holistic digital marketing strategy